Multifunctional Z‐scheme NaGdF4:Yb,Tm@ZnO/Ag3PO4 nanoheterojunction photocatalysts for water purification and antibacterial wound healing - Ran Yi; Changyuan Zhang; Dan Shan; Mengyu Di; Chen Li; Yu Wang; Yang Wu; Jing Zheng; Wenqi Liu; Baiqi Wang (View)
Abstract Photocatalysts with dual functionalities of decomposing organic pollutants in water and combating bacterial infections are increasingly important. Herein, NaGdF4:Yb,Tm@ZnO/Ag3PO4 (UZA) nanoheterojunction photocatalysts were synthesized via hydrothermal, sol–gel, and in situ deposition methods. The UZA photocatalyst demonstrated exceptional efficiency in generating reactive oxygen species (ROS), crucial for organic pollutant degradation. The incorporation of Ag facilitated efficient charge transfer in the all‐solid‐state Z‐scheme nanoheterojunction system. Furthermore, UZA exhibited potent antibacterial properties against both Gram‐positive Staphylococcus aureus (S. aureus) and Gram‐negative Escherichia coli (E. coli). The minimum bactericidal concentrations (MBC) of UZA were 50 µg/mL for S. aureus and 25 µg/mL for E. coli under natural irradiation, and 100 µg/mL for S. aureus and 25 µg/mL for E. coli under 980 nm irradiation, respectively. In vivo studies using a mouse model of acute bacterial‐infected wounds demonstrated that UZA incorporated into chitosan hydrogel dressings accelerated wound healing through photodynamic therapy within 9 days. The treated wounds exhibited rapid reduction to 9.95% of the initial area, diminished inflammatory responses, and enhanced re‐epithelialization attributed to sustained antibacterial effects and pathogen inhibition. Moreover, UZA composites showed excellent biocompatibility with a minimal hemolysis rate of 0.5% on erythrocytes. These findings underscore the promising application of UZA in water treatment for organic pollutants and in the treatment of skin wound infections caused by pathogenic bacteria.